PENDAMPINGAN UKS BERBASIS BASIC LIFE SKILLS UNTUK PENGUATAN KARAKTER REMAJA DI SMK AL ISHLAH PALANGKA RAYA - Tiara Lestari; Ikhtiar Zendrato; Zuly Daima Ulfa H.P.S; Uswatun Hasanah Purnama Sari; Abdullah; Siskaevia; Meiman Syukur Halawa H.P.S (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
This community engagement program aims to enhance adolescents' knowledge and skills regarding healthy living behaviors through the optimization of the School Health Unit (UKS) using a basic life skills approach at SMK Al Ishlah Palangka Raya. The program included a Focus Group Discussion (FGD) to establish a school-based UKS structure and appoint youth health cadres, followed by a basic life skills training and a culturally-based healthy school festival. The evaluation utilized digital instruments to assess participants’ knowledge and attitudes before and after the intervention. The results showed an increase in average knowledge scores from 64.9 (pre-test) to 70.8 (post-test). The highest score in behavioral attitudes was related to environmental health (82%), followed by personal hygiene and balanced nutrition, whereas daily physical activity and gadget use reduction remained low. The implementation of traditional sports in the school festival —such as “lari balok” and “hadang”— served as a means to reinforce students’ cultural identity and promote physical activity. The integrated approach, combining promotive and preventive health education with local wisdom, successfully supported character development and empowered students as agents of change in promoting a healthy lifestyle within and beyond the school environment. The implementation of a healthy school begins with simple actions, involves all stakeholders, utilizes both human and natural resources, and integrates local wisdom as a means of strengthening character development.